The Effectiveness of Simulation-Based First Aid Training on Improving Cognitive and Psychomotor Competence among Students of SMK Kesehatan Bakti Nusantara Gorontalo - ‎, ‎Setiawan (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
AbstractBackground: Simulation-based training is an effective learning method to enhance cognitive and psychomotor competence in first aid education. However, vocational health students often experience difficulties in translating theoretical knowledge into practical skills. Objective: This study aimed to analyze the effectiveness of simulation-based first aid training in improving the knowledge and skills of students at SMK Kesehatan Bakti Nusantara Gorontalo. Method: A pre-experimental one-group pre-test–post-test design was used with a total of 60 respondents. Knowledge and skills were measured before and after the intervention. Data were analyzed using paired statistical tests. Results: The findings showed a significant improvement in both domains. Knowledge scores increased from 63.25 ± 6.42 to 85.47 ± 4.83 (Δ = 22.22; p = 0.000). Skills scores increased from 68.10 ± 5.98 to 88.92 ± 5.26 (Δ = 20.82; p = 0.001). Both results indicate that simulation-based training effectively enhanced students’ cognitive and psychomotor abilities. Conclusion: Simulation-based first aid training significantly improves knowledge and skills among vocational health students. Integrating structured simulation activities into the curriculum is recommended to strengthen competency achievement and support students' preparedness in real emergency situations.Keywords: simulation-based training, first aid, knowledge, skills, vocational health students